141k views
0 votes
39. Rewrite each expression as an equivalent expression containing only one logarithm.

a. 3 ln(p + q) − 2 ln(q) − 7 ln(p)

1 Answer

3 votes

Answer:


ln{((p+q)^3)/(q^2p^7) }

Explanation:

3 ln(p + q) − 2 ln(q) − 7 ln(p)

=ln(p+q)^3- ln(q)^2-ln(p)^7

= ln(p+q)^3-{ln(q)^2+ln(p)^7}

=ln(p+q)^3-ln(q)^2*(p)^7

=ln{ (p+q)^3÷(q)^2*(p)^7}

=
ln{((p+q)^3)/(q^2p^7) }

User Kyle Parisi
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.